TANGGUNG JAWAB NOTARIS TERKAIT MINUTA AKTA YANG HILANG DITINJAU DARI UNDANG-UNDANG JABATAN NOTARIS - Wiwin Nurwianti; Rielly Lontoh; Amelia Nur Widyanti (Journal of Innovation Research and Knowledge, 2025)
The position of the minutes of the deed is very important so that the notary must be careful in storing it so that it is not damaged, lost and/or scattered. Negligence in storing the minutes of the deed results in the injured parties being able to sue the Notary for administrative, civil or criminal liability. The problems studied in this thesis are First, the legal consequences related to the lost minutes of the deed Second, the legal responsibility of the notary related to the lost minutes of the deed. The theories used to analyze these problems are the theory of legal consequences by R. Soeroso and the theory of responsibility by Hans Kelsen. The method used in this research is normative juridical research, namely library legal research or secondary data with primary, secondary and tertiary legal sources. The research approach used is a statutory approach, conceptual approach, analytical approach, and case approach and the technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, book literature, journals and other legal sources. For legal material analysis techniques carried out by grammatical and systematic legal interpretation while legal construction methods by analogy and legal refinement. From the results of the research, it can be concluded that the legal consequences for Notaries who are negligent in keeping the minutes of the deeds they make have juridical implications can be sued by the parties to compensate for losses, if the parties are harmed by the Notary concerned. The responsibility carried out by the notary due to damage or loss that occurs to the minutes of the deed that is lost or damaged due to the fault or negligence of the notary himself, the notary concerned will be held accountable in the form of making a report to the police for loss and damage, sending a report to the Minister of Law and Human Rights of the Republic of Indonesia regarding the condition of loss or damage and then waiting for follow-up settlement and if possible, the Notary can request an application from the Panel of Judges at the District Court to obtain approval for making a new copy of the deed.